Health risk assessment to dioxins, furans and PCBs in young children: The first French evaluation. (May 2020) - Hulin, Marion; Sirot, Véronique; Vasseur, Paule; Mahe, Aurelie; Leblanc, Jean-Charles; Jean, Julien; Marchand, Philippe; Venisseau, Anaïs; Le Bizec, Bruno; Rivière, Gilles
Abstract: A total diet study (TDS) was conducted between 2010 and 2016 to characterize the health risk related to chemical residues in food of French not breastfed children under three years of age (infant TDS). Among the targeted substances, polychlorinated dibenzo- p -dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs) and polychlorinated biphenyls (PCBs) have been characterized as they accumulate through the food chain, especially in lipid-rich food items, and because they have been associated with a number of adverse effects in humans. Food samples (n = 180) were collected to be representative of the dioxins and PCB exposure through the whole diet of non-breastfed children from 1 to 36 months old and prepared as consumed (including cooking) prior to analysis. Dietary exposure was then assessed for 705 representative children under 3 years of age based on their food consumptions recorded through a 3-consecutive-days record. Levels of PCDD/Fs and PCBs in infant food were lower than those observed in common food, leading to significant differences in exposure according to age groups. Mean exposures to PCDD/Fs ranged from 0.22 to 0.44 pg TEQWHO05 .kg bw −1 .d −1 (0.40–0.65 at the 90th percentile), depending on the age group and the hypothesis considered to manage left-censored data. Mean exposure to non-dioxin-like PCBs ranged from 0.87 ng kg bw −1 .d −1 (1.55 at the 90th percentile) in the 1–4 months old children to 3.53 ng kg bw −1 .d −1 (5.44 at the 90th percentile) in the 13–36 months old children. For dioxins and NDL-PCBs, the tolerable daily intake (TDI) was exceeded for some age groups, in particular for older ones. Therefore, appropriate management measures must continue for reducing exposure; it concerns mainly common milk in youngest children, ultra-fresh dairy products and fish. For PCBs, recommendations on fish consumption should be reminded. Moreover, toxicity studies focusing on mixtures of dioxin-like compounds should be encouraged in order to take into account effect of mixtures. Highlights: A total diet study focusing on non-breastfed children under 3 years of age was conducted in France for the very first time. This study aimed at evaluating the risk associated with exposure to chemical substances through food diet. PCDD/Fs and PCBs were detected in a large portion of the target food samples (between 49 and 100% of the samples analyzed). Situation has been identified as a concern for PCDD/Fs and PCBs after 6 months of age. Efforts should continue to reduce the exposure of the population.